Methods of Electro-Dynamic Stability Calculation of Flexible Bus-bars in High Voltage Switch Gears - I. I. Sergey; Y. G. Panamarenka; A. S. Mikhalyov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The improved vector-parametrical and simplified methods for calculation of electro-dynamic stability parameters of flexible busbars in high voltage switch gears have been presented in the paper. The developed methods and their software can be taken as a basis of methodological instructions on calculation of short-circuit current electro-dynamic action on flexible conductors of switching gears.